A comprehensive, integrated study of the clavicle: Its topographical anatomy, biomechanical architecture and function; pathological anatomy of mid-shaft fractures and the decision-making process for a surgical approach when planning an intramedullary implant: : Part 5 Frustum, a geometrical creation of a malunited clavicle fracture (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2026)
Highlights: Fractures of the clavicle within the shoulder complex are a two-bone problem, as the forces from the clavicle are mediated through the scapula to the glenohumeral joint. An angular malunion in the third-fifth and fourth sections of the clavicle from the sternal end often results in a frustum following conservative management of its fractures. This is reflected in subtle or gross winging of the scapula and dyskinesis, which affect the glenohumeral articulation. How biomechanical forces stimulate linear bone growth, which is mostly under compression, and correct torsional deformity at the cellular level in a mature callus, remains poorly understood. Whatever the ‘normal’ range of motion return in the adolescents with malunited clavicles, it is limited by remodelling potential and physical adaptations during recovery of muscle-length tension.This part of the study delves into the fundamentals of kinematic biomechanics pertaining to a malunited clavicle.